IDENTIFIKASI KANDUNGAN CANNABINOID DALAM EKSTRAK BATANG GANJA DENGAN METODE Al-TLC DAN HPTLC SPECTROPHOTODENSITOMETRY - Pitri Susanti, Ni Made (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
A research of identification of cannabinoid compounds of stems of cannabis sp was conducted. The aim of thisresearch was identified cannabinodes using TLC and HPTLC spectrophotodensitometry and confirmed by colortest. Cannabinoides of stems cannabis sp was extracted by maceration method by using ether as solvent.Concentrated extract was spotted on AL-TLC Si 60 G F 254 and also HPTLC Si 60 G F 254. Plates were elutedwith hexane-diethyl ether (80:20, v/v) in ascending on twin chember. Each peak was scanned on Camag TLCScannerIII, Identification of each insitu spectra were based on Rf and library spectra and confirmed by colortestby Fast Blue B salt.. The result showed that method can be used to identify the CBN, THC and CBD contentof marijuana stems.
Keywords: identification, cannabinoides, Al-TLC, HPTLC, spectrophotodensitometry